1995
DOI: 10.1136/sti.71.6.343
|View full text |Cite
|
Sign up to set email alerts
|

Yaws in Ecuador: impact of control measures on the disease in the Province of Esmeraldas.

Abstract: There was a corresponding decrease of 94*6% in the prevalence of dermal lesions (from 11-2% to 0*6%), and a reduction of 97.3% in latent infections (from 93.6% to 2.5%). Conclusions-The control of yaws using existing community-based health workers has proved very effective in Ecuador. (Genitourin Med 1995;71:343-346)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…As expected, the prevalence of TPPA positivity increased with age within the age group examined, and the study also confirmed previous reports8,13 that males are at slightly higher risk than females of both TPPA positivity and dual seropositivity. The reasons for this association are unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, the prevalence of TPPA positivity increased with age within the age group examined, and the study also confirmed previous reports8,13 that males are at slightly higher risk than females of both TPPA positivity and dual seropositivity. The reasons for this association are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Many countries report only clinical cases without laboratory confirmation and there are inadequate data to guide control programs in many countries. Previous studies have shown that the majority of clinical cases occur in children < 15 years of age, and have also suggested a preponderance of cases in males 3,8,13. It is also recognized that for every clinical case there are 5–6 individuals with serological evidence of infection but no clinical manifestations 8,13…”
Section: Introductionmentioning
confidence: 99%
“…After a single penicillin dose, early lesions become noninfectious after 24 hours and heal within 1 to 2 weeks. 64,67,68 PINTA Pinta, also known as puru-puru or carate, is an endemic treponematosis caused by Treponema carateum. The disease is characterized by a relatively benign course, chronic skin lesions, and no systemic involvement.…”
Section: Granuloma Inguinalementioning
confidence: 99%
“…As always, it is not known whether a lack of reported cases is the result of true disease elimination or lack of surveillance. In Ecuador, for example, no clinical cases were detected between 1993 and 1998, suggesting elimination of yaws (257,258). In Guyana, however, following the implementation of a control program in 2000, a resurvey conducted the following year showed a residual prevalence of yaws skin lesions of 1.6% (259).…”
Section: Yawsmentioning
confidence: 99%